User Experience Design for Nutrition Information Applications using Design Thinking - Fanani, Lutfi; Az-Zahra, Hanifah Muslimah; Akbar, Muhammad Aminul; Sianturi, Riswan Septriayadi (Department of Informatics Engineering, 2023)
A healthy diet serves as one of the aspects of one's fitness and understanding caloric value. The present study aims to design a user experience for mobile nutrition apps using Augmented Reality technology. Solutions are designed using design thinking stages, including empathize, define, ideate, prototype, and testing. Data related to reasons, frustration, goals, and target users are collected at the empathize stage. At the define stage, the empathy map and Personas are created. A prospective user journey map and information architecture are generated in the ideating stage. Wireframe and mockups are generated in the prototype stage. Finally, usability testing (i.e., task scenarios) evaluates the learnability (100%) and efficiency (0.067 goals/sec) aspects, and SUS assesses the satisfaction aspect. The satisfaction aspect score was 85, indicating a high acceptability level, B grade scale, and excellent adjective rating.